Sample exercises in critical reading for elementary grades a seminar paper - Espino, Demetrio N. 1934- ([Quezon City s.n.], 1967)
The author constructed graded exercises aimed at developing critical reading ability. The exercises from each grade level are made into a three-step process; that is, from controlled, then mixed controlled, to free response (uncontrolled). The attempt is to present the exercises from easy to difficult, from simple to complex, from controlled to free response.
Thesis (M.A.T.Reading)--University of the Philippines.
Keywords: Reading (Elementary).